A multi-objective optimization framework for treatment planning of permanent prostate brachytherapy - Selga, Cyrus Angelo (2010)
According to statistics from the Department of Health, prostate cancer is the 2nd leading cancer case among Filipino men. An effective treatment strategy is radiation therapy, wherein radiation is delivered to the prostate while attempting to minimize exposure to the nearly organs. Radiation therapy can be delivered either through an external nean or internally using radionuclide sources, the latter technique being called brachytherapy.